A multiproxy study of intertidal surface sediments from two macrotidal estuarine systems (Canche, Authie) in northern France: Insights into environmental processes. (15th November 2021) - Voltz, B.; Denis, L.; Duong, G.; Santoni, A.-L.; Artigas, L.F.; Cornille, V.; Henry, F.; Mathieu, O.; Tallobre, C.; Gontharet, S.
Abstract: Estuaries are considered one of the most dynamic ecosystems in the world, ensuring high production and transfer of large quantities of organic matter (OM) from continents to the ocean. Despite the large influence of estuaries in the functioning of coastal ecosystems, our understanding of OM dynamics in these buffering coastal environments remains fragmented. In this frame, our study was carried out to describe and understand the main drivers of OM distribution in two estuaries (Canche, Authie) of the eastern English Channel, based on descriptive and quantitative approaches. For this purpose, in February and March 2018, surface sediments were sampled at low tide along cross-shore transects in the intertidal zone of each estuary. Analysis of sediment grain size, porosity, proportion of aggregated particles, total carbonate content and organic geochemical characteristics (total OM content, atomic TOC/TN ratio, δ 13 C value) of surface sediments allowed identifying four biosedimentary facies: sand flat, mud flat, low and high salt marshes. In parallel, the elemental and isotopic characterization of the suspended particulate OM inputs by the rivers, the surface biofilms and the halophytic vegetation was performed to trace the three major sources contributing to sedimentary OM in both estuaries. Spatial distribution of OM in surface sediments (ranging between 0.6 and 26.9% dry weight) evidenced higher contents along marsh platforms than in sand and mud flats. and the OM pool was mainly constituted of a mixing of C3 terrestrial vascular plants, marine and riverine phytoplankton. The comparison between both estuaries highlighted that the geomorphology impacted by natural and anthropic factors plays a preponderant role in the distribution and the sources of sedimentary OM by influencing vegetation communities and hydrodynamic processes. In the context of sea level rise, an improved understanding of the OM dynamics within each biosedimentary facies is crucial to better constrain and assess the role of macrotidal estuaries in carbon cycle. Highlights: Field observation and physico-chemical analyses of exhaustive surface sediment samples used for determining biosedimentary facies. Source of sedimentary organic matter defined by elemental and isotopic proxies. Influence of the structure and texture of surface sediments on OM distribution. Principal Components Analysis highlighted two contrasted geomorphological stages.